2020
DOI: 10.1088/1741-2552/ab937e
|View full text |Cite
|
Sign up to set email alerts
|

Self-adaptive shared control with brain state evaluation network for human-wheelchair cooperation

Abstract: Objective. For the shared control systems, how to trade off the control weight between robot autonomy and human operator is an important issue, especially for BCI-based systems. However, most of existing shared controllers have paid less attention to the effects caused by subjects with different levels of brain control ability. Approach. In this paper, a brain state evaluation network, termed BSE-NET, is proposed to evaluate subjects’ brain control ability online based on quantized attention-gated kernel reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…It is still a challenge to drive robotic devices directly through BCI because this puts a large mental burden on users. To improve the performance of brain-actuated systems, the shared control strategy has been widely discussed and investigated [3] , [19] , [20] , [21] . Generally, a shared control architecture is conceived to integrate user commands (generated by cognitive intention) and robotic autonomy [17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is still a challenge to drive robotic devices directly through BCI because this puts a large mental burden on users. To improve the performance of brain-actuated systems, the shared control strategy has been widely discussed and investigated [3] , [19] , [20] , [21] . Generally, a shared control architecture is conceived to integrate user commands (generated by cognitive intention) and robotic autonomy [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Shared control is a control strategy that combines human control intention and robotic autonomous intelligence and can adapt to environmental changes, allowing users to participate in the interaction more effectively and with less workload [18] . Shared control arbitrators have been designed to use fixed weights [3] , distance-based weights [19] , and other methods [20] , [21] to fuse different control signals. These studies have demonstrated that the adoption of shared control could take advantage of human intention and robotic autonomous intelligence to improve the performance of BCI systems in a complex environment.…”
Section: Introductionmentioning
confidence: 99%
“…From the admissible velocities within this dynamic window, the combination of translational and rotational velocities is selected by maximizing an objective function. While there have been a few attempts to apply this approach to wheelchairs [51][52][53][54][55][56][57][58], notable drawbacks include increased computational costs and latency, particularly as the environment becomes more complex. Another widely employed approach for mobile robots is the potential fields method (PFM), with a prominent implementation known as the virtual force field (VFF).…”
Section: Related Workmentioning
confidence: 99%